EVALUASI PENAMBAHAN JUMLAH LANTAI PADA GEDUNG PERKULIAHAN FAKULTAS TEKNIK UNIVERSITAS JEMBER - Hari Subagio; Krisnamurti; Paksitya Purnama Putra (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Learning facilities for students of the Faculty of Engineering, University of Jember (FT-UNEJ) were still insufficient. Fifteen study programs at FT-UNEJ were only served in one lecture building. Additional floors in existing buildings are done to increase the classrooms as a follow to the problem. An additional three floors were made as a classroom and one roof as a meeting room (rooftop). Planning and evaluation were done by modeling 3D buildings in a structural analysis program. Analysis and evaluation in the structural analysis program were modeled with the same dimensions as the existing conditions, and an additional number of floors would be added according to the preliminary design calculations. Modeling results showed the condition of the building plans was still safe. The largest inter-floor deviation value is 10.2 mm which is still below the permit deviation (31.5 mm), and the structural integrity value is -0.97 (requirement -1 <- 0.97 <1).